Perancangan video promosi distro Ulek Bulu Clothing Lubuk Begalung Padang - Fahri Syahputra, Dr. Syafwandi, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The purpose of this article is to produce a promotional media package for Ulek Bulu Distro Clothing Lubuk Begalung Padang. This design aims to create a promotion design more effectively and efficiently, and can reach a broad target audience by being uploaded on social media. In addition, the presence of this promotional video can later show Ulek Bulu Clothing products so that they can optimize the promotion in introducing Ulek Bulu Clothing distro to the target audience. The method used to produce the design is a research-based design of observation data collection directly to the location of the Ulek Bulu Clothing distro. The design of the promotional video for Ulek Bulu Clothing Lubuk Begalung Padang distro produced a promotional media package, namely: video as the main media while supporting media in the form of: Backdrop, Banner, Sticker, Calendar, Poster, Flag Chain and Name Card.Keywords : Designing, Ulek Bulu Clothing and Promotional Video.